The effects of social media on grammar competence among undergraduates in Universiti Tunku Abdul Rahman (UTAR) - Wong, Yew Heng (2020)
Social media is undoubtedly the most popular platform for online communications to be taken place among Malaysian undergraduates and undergraduates from the rest of the world. Majority of the activities on social media are conducted using English language as the primary and universal language. The exposure of English language on social media has deeply affected the development of grammar competence among the undergraduates as they create and consume social media content on a daily basis. On the other hand, the criticisms about Universiti Tunku Abdul Rahman (UTAR) undergraduates and their incompetence to communicate fluently in English language is a serious matter that cannot be overlooked anymore as it goes against UTAR’s mission to preserve a strong programme that cultivates brilliant undergraduates. Hence, the research adopted quantitative methodologies to study the important issues between social media and UTAR undergraduates, which including the usage of Internet slangs on social media, the grammar competence of the undergraduates, and the perception of the undergraduates on its effects. This research invited 150 UTAR undergraduates to participate in a survey session through the application of online questionnaire platform. Subsequently, different analysis methods were used to analyze the data gathered thoroughly in order to draw conclusions based on their responses. The findings of this research will definitely serve as a future reference for educators to understand the effects of social media on the grammar competence among UTAR undergraduates.